Totems of Czech Tramps - Kuligowski, Waldemar (Literatura Ludowa. Journal of Folklore and Popular Culture, 2026)
Reviev: Karel Altman, Dědictví českého tramping. Vybrané kapitoly z historie a každodennosti svérázného fenoménu, Akademia, Praha 2024.